2016
DOI: 10.1097/rct.0000000000000320
|View full text |Cite
|
Sign up to set email alerts
|

Difference Between HPV-Positive and HPV-Negative Non-Oropharyngeal Head and Neck Cancer

Abstract: Texture analysis demonstrated significant differences between HPV and HPV non-OPCs on computed tomography images, which may have a potential to prove morphologic feature differences among HPV-related tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 21 publications
0
49
0
Order By: Relevance
“…CT texture analysis is an emerging technique that quantifies heterogeneity of a region of interest by analyzing the distribution and/or relationship of pixel or voxel gray levels in the image [17]. This technique has been most intensely studied in oncologic applications, and has shown association with pathologic features and clinical outcomes in a variety of tumor types [18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Some non-oncologic applications are being evaluated, with several groups using texture analysis to assess emphysema and fibrosis in the lung [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…CT texture analysis is an emerging technique that quantifies heterogeneity of a region of interest by analyzing the distribution and/or relationship of pixel or voxel gray levels in the image [17]. This technique has been most intensely studied in oncologic applications, and has shown association with pathologic features and clinical outcomes in a variety of tumor types [18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Some non-oncologic applications are being evaluated, with several groups using texture analysis to assess emphysema and fibrosis in the lung [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Convincing evidence has shown that HPV‐positive and HPV‐unrelated (HPV‐negative) OPC have unique demographics profiles, clinical presentations, and prognoses. Several studies have also reported radiologic differences between both entities . However, most studies were limited by relatively small sample sizes and subject to selection bias as well as interrater and intrarater variation in assessing various radiologic features.…”
Section: Introductionmentioning
confidence: 99%
“…The morbidity and mortality of human papilloma virus (HPV)‐positive oropharyngeal squamous cell carcinoma were higher than those of HPV‐negative oropharyngeal squamous cell carcinoma. One study showed that CT imaging features can distinguish between HPV positive and HPV negative oropharyngeal squamous cell carcinoma and can be used to select appropriate treatment strategy 18 . In head and neck cancer, such as oropharyngeal head and neck squamous cell carcinoma and non‐oropharyngeal head and neck squamous cell carcinoma, different cell sublines have different radiosensitivity factors and different resistance to radiation.…”
Section: Application Of Radiomics In Radiotherapymentioning
confidence: 99%